Crop Based Community KVK - a Predictive Innovative Model of Technology Delivery to Reach the Unreached - Pandiyan, M; Hanif, Noorjehan A.K.A.; Senthil Kumar, M; Davidson, Joshua (Journal of Agricultural Extension Management, 2018)
Efforts have been made from time to time to raise the productivity of farmers through extension services but their objectives are still poorly met. The purpose of extension is to disseminate advice to farmers. Gaps in knowledge contribute to the yield gap in biophysical and economic settings. The current extension worker to farmer ratio is very wide in India and hence to address the particular crop in a particular block is very low. The Mandate of Krishi Vigyan Kendra and technology delivery is focussed to particular interventions and is not specific to crop based zone. Technology decision support system is not available within the crop zone and the farmers are unable to get the required knowledge. On the demand side, self-selection on the part of larger, more commercial farmers may bias outcomes. Extension service budgets may be inadequate. Issues of motivation, competence, performance and accountability of extension institutions and their agents may affect results. The main lacunae in reaching small and marginal farmers in rainfed areas for service delivery of technological information’s is limited staff. To overcome these constraints and fulfil demands of the farmers, the proposed predictive innovative model of Crop based Community KVK will certainly play a major role in transferring the technologies through training by creating farmer experts and shaping them as unique Cluster Crop Experts in the selected village clusters. Community KVK is an innovative conceptual model designed for technology delivery of farm information to the farming community in cluster villages by establishing similar set up of KVK in villages by training and networking of socially amicable farmers. Upscaling this model, can convert farmer Subject Matter Specialists into paid service consultants and they can excel in comparison to input dealers who do not possess crop based knowledge. Further, marketing linkage can be created through farmers groups like commodity groups, FIGs and other groups.